PENENTUAN NILAI SPF DARI EKSTRAK ETANOL DAUN KELOR (Moringa oleifera Lam) DAN DAUN KEMANGI (Ocimum basilicum L.) - Mirawati, Mirawati; Purnamasari M, Vina; Harliman, Isrhopana Kinana; Sahira, Sahira; Bade, Iskandar Zulkarnain Mahmud; Hasrawati, A.; Haq, Nasrul (Fakultas Farmasi UMI, 2025)
Excessive exposure to ultraviolet (UV) radiation can lead to various skin issues, ranging from premature aging to an increased risk of skin cancer. As a result, the exploration of natural ingredients for UV protection has gained growing attention in cosmetic research. This study aims to evaluate the UV-absorbing potential of ethanolic extracts from Moringa oleifera Lam leaves and Ocimum basilicum L. leaves by determining their Sun Protection Factor (SPF) values. Using spectrophotometric analysis across different concentrations, both extracts demonstrated significant potential as natural sunscreen agents. At a concentration of 1500 ppm, the highest SPF values were recorded at 45.683 for Moringa oleifera Lam and 47.037 for Ocimum basilicum L. These findings highlight the promising potential of both plant extracts as active ingredients in sun-protective skincare formulations